Methylation of breast cancer susceptibility gene 1 (BRCA1) predicts recurrence in patients with curatively resected stage I non–small cell lung cancer. Issue 4 (18th January 2013) - Harada, Hiroaki; Miyamoto, Kazuaki; Yamashita, Yoshinori; Nakano, Kikuo; Taniyama, Kiyomi; Miyata, Yoshihiro; Ohdan, Hideki; Okada, Morihito
Abstract BACKGROUND: Even after early detection and curative resection of early stage non–small cell lung cancer (NSCLC), a significant fraction of patients develop recurrent disease. Molecular biomarkers that can predict the risk of recurrence thus need to be identified to improve clinical outcomes. METHODS: Using the methylation‐specific polymerase chain reaction assay, promoter methylation of the breast cancer susceptibility gene 1 (BRCA1) was assessed in cancer tissues from 70 patients with curatively resected stage I NSCLC. The clinical relevance of BRCA1 methylation status was evaluated in terms of outcome of the disease. RESULTS: Methylation of the BRCA1 promoter was detected in 13 of 70 patients (18.6%). Multiple logistic regression analysis revealed that BRCA1 methylation was an independent risk factor for recurrence (P = .0197) and that patients with BRCA1 methylation demonstrated significantly poorer recurrence‐free survival compared to those without (P = .0139). Cox's proportional hazard regression analysis revealed that BRCA1 methylation was an independent risk factor for recurrence‐free survival (P = .0155). CONCLUSIONS: Methylated BRCA1 can be a potential biomarker that predicts the prognosis after curative resection of stage I NSCLC. Considering that BRCA1 plays a role in chemotherapy‐induced apoptosis, it is plausible that identification of methylated BRCA1 could provide information that is clinically relevant to tailored adjuvant therapy. Cancer 2013. © 2013 American Cancer Society.